Multimodal analysis of playback theater: experiences of Triqui-Traque UNA Playback Theater Company - León-Páez Brealey, Diego (2024)
This paper analyzes the elements of multimodality present in playback theater (PBT) and how these influence the social construction of meaning within the groups and communities with which it works. The present paper is the result of a research process aimed at exploring the multimodal elements of PBT, based on the experiences of Triqui-Traque (from Department of Psychology, Universidad Nacional) working with groups and communities, and particularly, the analysis of a workshop-performance conducted in March 2020 at a non-governmental organization (NGO) dedicated to the care and well-bieng of children and adolescents in Costa Rica. This is an applied, qualitative and exploratory study in which the video of the NGO´s workshop-performance was analyzed in depth. The analysis focuses on the construction of meaning through PBT, and not on the psychological and social elements of the shared stories or the process of re-signification by the audience. It is concluded that the multimodal perspective applied to PBT helps to clarify the elements that converge in the communicative proposal of Triqui-Traque, where canvases and sub-canvases such as bodies, music, and movement intertwine. These elements, in a synergistic, ergodic, and mutable way, constitute a multimodal communicative proposal that contributes to the social construction of meaning in a PBT performance.